Two models of accessibility to railway traveling for vulnerable, elderly persons. (August 2015) - Sundling, C.; Emardson, R.; Pendrill, L.R.; Nilsson, M.E.; Berglund, B.
Highlights: Accessibility is modeled from functional ability, barriers and travel behavior. Accessibility can be measured by individual weighting of sets of barriers. By reducing appreciable barriers, functional ability will be improved. Improved ability leads to independent travel behaviors and increased accessibility. Abatement procedures should be advised for better accessibility for all . Abstract: Public transport mobility is restricted for the vulnerable travelers, e.g., those with functional limitations. By removing barriers, a more flexible and independent travel behavior is accomplished. For whole-trip traveling, we model accessibility as a three-way reciprocal relationship among travelers' functional ability, barriers met and resulting travel behaviors. For every journey and destination, an accessibility measure is constructed from all barriers' weights and the probabilities of encountering each of them in traveling to specific destinations. The accessibility to whole-trip traveling is then modeled by travelers' individual weightings of sets of barriers and the probabilities of encountering them. By using specific reference values, as in master scaling, we estimate the measurement error for each participant's perceived effort to overcome a certain barrier, and thus obtain a calibrated measure of accessibility. We conclude that customized abatement procedures must accomplish better accessibility for all, especially for the vulnerable travelers.